2004
DOI: 10.1007/s00299-003-0703-9
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of Chrysanthemum morifolium ( Dendranthema grandiflora Ramat.) using different approaches

Abstract: Chrysanthemum species are grown both as ornamentals and for the production of pyrethrum. Recent increased production and breeding efforts have raised the need for the conservation of valuable germplasm. Chrysanthemum has been cryopreserved by controlled-rate-freezing as early as 1990. We report here deep-freezing of shoot tips of C. morifolium var. Escort by different technical procedures: controlled-rate-freezing, encapsulation/dehydration, ultra-rapid-freezing by the droplet method and vitrification. While v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 6 publications
2
24
1
Order By: Relevance
“…Water content decrease is achieved by preculturing explants with osmotic compounds, air desiccation or vitrification. On bases, vitrification (Sarkar & Naik, 1998), droplet (SchaferMenuhr et al, 1996) and recently vitrification-droplet (Halmagyi et al, 2004;Schafer-Menuhr et al, 1996) methods were developed or adapted for potato.…”
Section: Methods Based On Dehydrationmentioning
confidence: 99%
“…Water content decrease is achieved by preculturing explants with osmotic compounds, air desiccation or vitrification. On bases, vitrification (Sarkar & Naik, 1998), droplet (SchaferMenuhr et al, 1996) and recently vitrification-droplet (Halmagyi et al, 2004;Schafer-Menuhr et al, 1996) methods were developed or adapted for potato.…”
Section: Methods Based On Dehydrationmentioning
confidence: 99%
“…Although no further genetic analysis of the variant material was done in that study, the authors concluded that these results should be taken into consideration when cryopreserving chrysanthemum. The same recommendation was done some years later by Halmagyi et al (2004) in their work on cryopreservation of chrysanthemum using different approaches. They suggested that comparative investigations of genetic stability and cryo-injury should be carried out.…”
Section: Stability In Cryopreserved Chrysanthemum Culturesmentioning
confidence: 79%
“…Fukai and Oe (1990) demonstrated that after controlled freezing only a small part of the apex survived and that treatment with DMSO (2 days culture on medium with 5% v/v DMSO, and then incubated for 1h at 0 ºC with 10% DMSO) caused abnormal leaf development. In other cryopreservation works the possible adventitious origin of the recovered shoots is stated (Halmagyi et al 2004, Fukai et al 1991. Hitmi et al (1999aHitmi et al ( , 2000a reported no callus formation in recovered shoot from cryopreserved apices.…”
Section: Chrysanthemum Cryopreservationmentioning
confidence: 99%
See 2 more Smart Citations